Communication Patterns in Equipping Foster Children to Face the Challenges of the 5.0 Era (Case Study: Seroja Children's Social Rehabilitation Service Center, Bone Regency) - Rusnali, Andi Nur Aisyah; Erlangga, Dian (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This research examines the communication patterns of caregivers in equipping foster children to face the challenges of the 4.0 era at the Seroja Children's Social Rehabilitation Service Center (PPRSA), Bone Regency, South Sulawesi. The aim of this research is to determine the communication patterns used by caregivers to equip foster children to face the 4.0 era as well as the supporting and inhibiting factors in the training process. Communication patterns are the focus of research in this paper. This research uses field research methods where subjects are researched through interviews, observation and documentation. Using cybernetic theory, researchers examine the relationship between communication patterns and the training process towards the 4.0 era. The qualitative descriptive analysis method was used to analyze the data collected from the research. The results of the research show that there are four patterns of caregiver communication in equipping caregivers for the 4.0 era, namely a) wheel pattern, b) star pattern, c) individual communication, and d) group communication. 2) Factors that support the process of providing foster children include availability Wifi facilities and proximity to foster children. Meanwhile, the factors that hinder this process are the lack of Smartphone facilities so they have to take turns using them. The research is expected to be able to contribute to the development of communication science in the future.